Vaiśeṣikasūtra - a translation - Kaṇāda ca. 1./2. Jh. (Routledge Hindu studies series, 2022)
1. Introduction to Indian Philosophy and Vaiśeṣika -- 2. Sources and Resources on Vaiśeṣikasūtra -- 3. Vaiśeṣikasūtra: Transliteration and Translation -- Appendixes -- Bibliography -- Index on Sanskrit terms with Glossary.